PENGARUH KEPUASAN KERJA DAN GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP TURNOVER INTENTION DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MEDIASI STUDI KASUS PADA CV. INDOJATI - Anisa Ayu Gyanmar, Fridasari; Achmad, Nur (MANAJEMEN DEWANTARA, 2024)
Employee presence is a key element in driving organizational activities and optimizing the use of existing resources to achieve orientation. Research findings show consistency in the relationship between turnover intention and factors such as leadership, intelligence, employee behavior in carrying out tasks outside the main task (extraroles), job dissatisfaction, and experiences related to organizational commitment. The method applied in the following research applies a quantitative approach. The population identified includes employees in the CV production department. Indojati, taken by 80 people. Data analysis was carried out using Jeffreys's Amazing Statistics Program (JASP) software. Research findings show that it is. Job satisfaction has a positive and significant effect on turnover intention. Transformational leadership style is known to influence turnover intention significantly positively. Organizational commitment mediates the effect of job satisfaction on turnover intention. Transformational leadership style can mediate organizational commitment with turnover intention. Suggestions for future researchers can be to use other variables that can be studied significantly regarding the influence of turnover intention. Variables that are not applied in the following research should be applied or added to further research. Future researchers can research other organizations or service industries.